Calculation of the actuator system in swash plate axial piston machines by a coupled multibody and TEHL simulation. (May 2022) - Kroneis, Markus; Scheerer, René; Bobach, Lars; Bartel, Dirk
This paper presents a method for coupling a multibody simulation for the actuator system in axial piston machines in combination with a transient, three-dimensional, thermal elastohydrodynamic contact calculation. For the tribological investigation, the oscillating piston/cylinder contact is focused, whereby a simplified model of the actuator system simulates the loads. The developed method allows the integration of a complex tribological contact simulation under mixed friction conditions into a dynamic multibody simulation based on the Newton–Euler method. It is discussed how the accuracy of the results and the calculation time can be improved by the procedure.